THE DEPICTION OF RELIGIOUS CONFLICT IN BHAGAT’S THE GIRL IN ROOM 105 - Ishaq, Maulana; Marsih, Linusia (Anaphora : Journal of Language, Literary, and Cultural Studies, 2021)
This study aims to discuss the issue of religious conflict in Bhagat’s The Girl in Room 105. The objectives of this study are to analyze the religious conflicts and characteristics of the religious conflict reflected in the novel. This study uses descriptive qualitative method using sociological approach and several theories of religious conflict. The result, this study depicts the religious conflicts between by Muslim and Hindu as well as the characteristics of the religious conflict. The religious conflicts are presented in the sphere of belief: conflict between Muslim and Hindu, ideology: conflict between Kashmiri and Indian, organization: conflict between separatist groups of Kashmir against Indian government, family: conflict between Keshav and Zara’s family, and individual: conflict between Zara and Keshav.